Outcome based education: a computational measurement on special librarian intelligence competency / Azrilah Abdul Aziz, Sohaimi Zakaria and Johari Jamaluddin - Abdul Aziz, Azrilah; Zakaria, Sohaimi; Jamaluddin, Johari (Centre for Media and Information Warfare Studies, 2008)
Information is the key driver for an organization to be able to make prudent decision and direct the organization effectively to meet their corporate objectives. With the advent of information technology and information systems, dissemination of knowledge, data, and information, has exploded by leaps and bounds. Librarians are now expected to conduct data mining, explore and analyze meta data, code and categorize knowledge, employing the most advance information management system as well as the best available technology. Now, they need to be equipped with specific competency to execute responsibilities vested on them. This has prompted the need to study Library and Information Management program offered by the Faculty of Information Management, Universiti Teknologi MARA, Malaysia (UiTM) . The program was designed to develop competent Librarians; among others the graduate outcomes is to be Knowledge Managers, Information Innovator; etcetera, which are deemed Information Professionals (IP). This is explicitly described in the subject learning outcomes where technical knowledge and generic skills were identified using Blooms Taxonomy. This paper presents a case study on special librarians who is required to carry out specific task in a highly specific environment. Result of computational measurement of course learning outcomes is mapped against job specification in the industry utilizing competencies attributes established from meta-analysis. It was noted that development of technology and expansion of current job scope demands a specific training for these special librarians.